AB0111 The Underlying Pathogenic Effect of Impared Dnase I Activity on Rheumatoid Arthritis. (15th July 2016) - Xu, X.; Shen, H.
Abstract : Background: Aberrant formation of neutrophil extracellular traps (NETs) play important role in the pathogenesis of rheumatoid arthritis (RA) and Deoxyribonuclease I (DNase I) can remove NETs in vivo. Objectives: We aimed to investigate the underlying pathogenic effect of DNase I on RA. Methods: Serum DNase I activity was measured by radial enzyme diffusion method in 83 RA patients and 60 healthy volunteers, synovial fluid (SF) from 27 RA patients and 38 other inflammatory arthritis patients was measured by the same way. The SF cfDNA level was measured by Pico Green Kit. Correlation analysis were performed between DNase I activity, cfDNA level and clinical parameters of RA patients. Results: Serum DNase I activity was significantly lower in RA group than in healthy control group [0.2913 (0.2029, 0.4064)U/ml vs 0.3980 (0.2864, 0.5484)U/ml, P<0.001] and negatively correlated with ESR (r=-0.2862, P=0.0122), CRP (r=-0.2790, P=0.0184) and neutrophil cell counts (r=-0.287, P=0.011). SF DNase I activity in RA group, ankylosing spondylitis (AS) group and gouty arthritis (GA) group were almost negative. SF cfDNA level in RA group was significantly higher than that in OA group [40.00 (12.47, 163.22) ug/ml vs 9.27 (4.62, 17.58) ug/ml, P=0.002], but there were no significant difference when compared to AS group [36.80 (4.84, 84.82) ug/ml, P=0.428] and GA group [156.72 (89.81, 257.11) ug/ml, P=0.132]. In inflammatory arthritis patients, SF cfDNA level was positively correlated to ESR (r=0.4106, P=0.0116)and CRP (r=0.5747, P=0.0002). Conclusions: Impairment of DNase I activity may be responsible for the enhanced NETs generation and involve in the pathogenesis of RA. References: Holers VM. Autoimmunity to citrullinated proteins and the initiation of rheumatoid arthritis[J]. Curr Opin Immunol, 2013, 25(6):728–35. Khandpur R, CarmonaRivera C, VivekanandanGiri A, et al. NETs are a source of citrullinated autoantigens and stimulate inflammatory responses in rheumatoid arthritis [J]. Sci Transl Med, 2013, 5(178): 178ra40. Pratesi F, Dioni I, Tommasi C, et al. Antibodies from patients with rheumatoid arthritis target citrullinated histone4 contained in neutrophils extracellular traps[J]. Ann Rheum Dis 2014, 73(7):1414–22. Sur Chowdhury C, Giaglis S, Walker UA, et al. Enhanced neutrophil extracellular trap generation in rheumatoid arthritis: analysis of underlying signal transduction pathways and potential diagnostic utility[J].Arthritis Res Ther, 2014;16(3):R122 Gupta AK, Hasler P, Holzgreve W, et al. Induction of neutrophil extracellular DNA lattices by placental microparticles and IL- 8 and their presence in preeclampsia [J].Hum Immunol, 2005, 66(11): 1146–54. Hakkim A, Furnrohr BG, Amann K, et al. Impairment of neutrophil extracellular trap degradation is associated with lupus nephritis [J]. Proc Natl Acad Sci U S A, 2010, 107(21): 9813–18. Disclosure of Interest: None declared